Nutritional Analysis of Starfruit-based Nata: Macronutrient composition and Potential as Functional Food - Juwita, Ratna; Manggara, algafari Bakti; Rahmi, Hanif Nabila; Wahyuni, Endang; Diva, Dhea Amalia Putri; Fadmasari, Alfrida Parma (The Journal of Pure and Applied Chemistry Research, 2025)
Non-communicable diseases in the community are often linked to dietary factors. Consuming functional foods can help prevent these diseases. Functional foods can be categorized into three types: unmodified, modified, and prebiotic food. Nata is a fermented food that is rich of fiber, and able to act as a prebiotic. Starfruit (Averrhoa carambola) is a nutritious fruit with potential for various food products, but it is often underutilized. This study explores the possibility of making nata using starfruit, with variations in added liquid: coconut water, palm fruit water, a mixture of both, and mineral water. The macronutrient content (fiber, protein, and fat) of these nata variations was analyzed to assess their nutritional value. The results showed that nata made with coconut water exhibited the highest dietary fiber content (6.93%). Nata made with a combination of coconut water and palm fruit water has the highest protein content (0.48%), and nata made with palm fruit water has the lowest fat content (0.31%), respectively. This finding paves the way for further study in applicating starfruit based functional food products.